A Multivariate Twin Study of Hippocampal Volume, Self-Esteem and Well-Being in Middle Aged Men - Kubarych, Thomas S. (2012)
Self-esteem and well-being are important for successful aging, and some evidence suggests that self-esteem and well-being are associated with hippocampal volume, cognition, and stress responsivity. Whereas most of this evidence is based on studies of older adults, we investigated self-esteem, well-being and hippocampal volume in 474 male middle-age twins. Self-esteem was significantly positively correlated with hippocampal volume (.09, p=.03 for left hippocampus, .10, p=.04 for right). Correlations for well-being were not significant (ps ≫.05). There were strong phenotypic correlations between self-esteem and well-being (.72, p<.001) and between left and right hippocampal volume (.72, p<.001). In multivariate genetic analyses, a 2-factor AE model with well-being and self-esteem on one factor and left and right hippocampal volumes on the other factor fit the data better than Cholesky, independent pathway or common pathway models. The correlation between the two genetic factors was .12 (p=.03); the correlation between the environmental factors was .09 (p>05). Our results indicate that largely different genetic and environmental factors underlie self-esteem and well-being on the one hand and hippocampal volume on the other.